2012
DOI: 10.1016/j.janxdis.2011.08.011
|View full text |Cite
|
Sign up to set email alerts
|

A pilot feasibility evaluation of the CALM Program for anxiety disorders in early childhood

Abstract: As many as 9% of preschoolers suffer from an anxiety disorder, and earlier onset of disorder is associated with more intractable forms of psychopathology in later life. At present there is a relative dearth of empirical work examining the development of evidence-based treatments for anxiety disorders presenting in early childhood. Building on previous work supporting extensions of PCIT for separation anxiety disorder, the present study examines the preliminary feasibility and efficacy of an anxiety-based modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 66 publications
1
49
0
2
Order By: Relevance
“…This approach has increased the reliability of the results by making the assessment more objective. In our study, the increased CGAS scores after intervention were in line with other patent-only CBT studies [17,18,36,39]. Even though CGAS has been a commonly used scale in these studies, CGI-S has rarely been used.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This approach has increased the reliability of the results by making the assessment more objective. In our study, the increased CGAS scores after intervention were in line with other patent-only CBT studies [17,18,36,39]. Even though CGAS has been a commonly used scale in these studies, CGI-S has rarely been used.…”
Section: Discussionsupporting
confidence: 91%
“…Stigma is one of the most important trammel for psychological treatment applications and parents consider that their children to be more vulnerable than their parents for stigmatization [15] so parent-focused intervention may be more acceptable than child-focused therapy and in this content, working with parents is a promising treatment strategy. In recent years, as an alternative to child-focused CBT, some parent-based CBT interventions have been found to be effective in reducing symptoms in children with anxiety disorders [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Such parenting may inadvertently further maintain anxiety by preventing the child from fully engaging in anxiety-provoking situations that would enable the child to test and alter maladaptive cognitions regarding fear-eliciting stimuli (Dadds & Barrett, 2001; Wood, Piacentini, Southam-Gerow, Chi, & Sigman, 2006). For this reason, supported family-based treatments for childhood anxiety often target the reduction of parental intrusiveness/overinvolvement as a core treatment aim (e.g., Barrett, Dadds, & Rapee, 1996; Comer et al, 2012; Kendall, Hudson, Gosch, Flannery-Schroeder, & Suveg, 2008). …”
mentioning
confidence: 99%
“…Given observed moderating effects of age within middle childhood and adolescence on parent and child anxiety in cross-sectional work (Verhoeven, Bogels, & van der Bruggen, 2012), as well as the growing recognition of peer relationships in psychological functioning in adolescence (Prinstein & La Greca, 2002; Siegel, La Greca, & Harrison, 2009), it is particularly important to investigate both the effects of early parenting on the trajectory of anxiety across childhood and cross-sectional relationships between paternal behavior and child anxiety in a cohort followed through middle childhood. Specifically, the investigation of these relationships at key developmental time points, including the initiation of full-time schooling (age 6) and later in the elementary years, will also serve to inform parent-directed content of child anxiety interventions targeted in early childhood populations (e.g., Comer et al, 2012; Hirshfeld-Becker et al, 2010), as well as those designed to treat children age 7 through age 17 (e.g., Kendall et al, 2008). …”
mentioning
confidence: 99%
“…62,63 A randomized controlled trial demonstrated that modified PCIT was effective in helping parents recognize emotions, although not better than parent education in reducing depressive symptoms. 74 Significant controversy and limited data about the validity of diagnostic criteria for bipolar disorder remain, and no rigorous studies of nonpharmacologic interventions in this age group exist.…”
Section: Infants and Toddlersmentioning
confidence: 99%